THE EFFECTS OF TED TALK VIDEOS ON EFL SPEAKING PERFORMANCE - Tusino Tusino; Nur Inayati Amrina Rosyada; Titi Rokhayati; Tengku Intan Suzila Tengku Sharif (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2023)
Abstract: This study aims to describe the effect of TED Talk videos on speaking performance and to reveal the students’ perceptions toward the use of TED Talk in EFL speaking class. This study employed a quasi-experimental design with seventy-two secondary school students in Indonesia. The data were collected through tests and closed-ended questionnaires. The result of this research showed that after the treatment, there was a different speaking performance between students taught using TED Talk video and those without using TED Talk video. It was found that the mean of post-test in the experimental group was 75.17; meanwhile, the mean of post-test in the control group was 72.94. The result of the t-test analysis showed that the Sig. (2-tailed) value was lower than 0.05 (0.032<0.05). The questionnaire results revealed that students had good perceptions toward the use of TED Talk videos in learning speaking. It can be concluded that there was a significant effect